2016
DOI: 10.4103/2303-9027.191664
|View full text |Cite
|
Sign up to set email alerts
|

Endosonographic examination of thyroid gland among patients with nonthyroid cancers

Abstract: Objectives:There is limited endosonographic literature regarding thyroid gland pathology, which is frequently visualized during upper endoscopic ultrasound (EUS). Our objective was to assess the prevalence of benign and malignant thyroid lesions encountered during routine upper EUS within a cancer center setting.Materials and Methods:The data were prospectively collected and retrospectively analyzed. All upper EUS procedures performed between October 2012 and July 2014 were reviewed at a large referral cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In this study, one FNA (11%) was able to confirm metastatic RCC (under transcutaneous ultrasonographic guidance), whereas all six core needle biopsies confirmed metastatic RCC. Alkhatib et al [ 9 ] described the first study that evaluated the endosonographic findings of the thyroid gland during a routine upper EUS in 100 cases. The results of the study showed thyroid lesions in 12 cases, out of which three previously undiagnosed thyroid cancers were visualized during EUS (two primary papillary thyroid cancers and one anaplastic thyroid cancer).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one FNA (11%) was able to confirm metastatic RCC (under transcutaneous ultrasonographic guidance), whereas all six core needle biopsies confirmed metastatic RCC. Alkhatib et al [ 9 ] described the first study that evaluated the endosonographic findings of the thyroid gland during a routine upper EUS in 100 cases. The results of the study showed thyroid lesions in 12 cases, out of which three previously undiagnosed thyroid cancers were visualized during EUS (two primary papillary thyroid cancers and one anaplastic thyroid cancer).…”
Section: Discussionmentioning
confidence: 99%